Клінічні та біохімічні дослідження терапевтичної ефективності дієтичної добавки фітосил-Р - Kartel, M. T.; Viltsaniuk, O. A.; Barvinchenko, V. M.; Lipkovska, N. O.; Viltsaniuk, O. O. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2016)
The results of clinical and biochemical studies demonstrated the therapeutic efficacy of dietary supplement Phytosil-R in the complex treatment of patients with acute intestinal obstruction and explained it by high sorption capacity of this preparation towards infectious and toxic agents and directed therapeutic action of the highly dispersed native medicinal plants. It was shown that Phytosil-R provides maximum removal of pathogenic microflora, its toxic waste products, and creates optimal conditions for the restoration of the barrier function of the intestinal wall, the removal of endogenous intoxication and elimination of enteric disease. The application of Phytosil-R preparation showed its good tolerability, abcence of contraindications, side effects and allergic reactions.